The A to Z of corporate social responsibility : a complete reference guide to concepts, codes and organisations - Visser, Wayne (Chichester : John Wiley & Sons, 2007)
This is the world's first complete reference on CSR, compiled by the Institute for Corporate Cultural Affairs (the ICCA). The entries, from AA 1000 Series of Standards on Accountability to Zen, have been written by leading experts, leading global thinkers and CSR practitioners.
A-Z.
John Wiley and Sons
Keywords: Social responsibility of business; Entreprises; Social responsibility of business